2024
DOI: 10.3390/ani14050743
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cyanide Poisoning in Cattle from Sorghum halepense and S. bicolor Cultivars in Northwest Italy

Stefano Giantin,
Alberico Franzin,
Fulvio Brusa
et al.

Abstract: Sorghum plants naturally produce dhurrin, a cyanogenic glycoside that may be hydrolysed to cyanide, resulting in often-lethal toxicoses. Ruminants are particularly sensitive to cyanogenic glycosides due to the active role of rumen microbiota in dhurrin hydrolysis. This work provides an overview of a poisoning outbreak that occurred in 5 farms in Northwest Italy in August 2022; a total of 66 cows died, and many others developed acute toxicosis after being fed on either cultivated (Sorghum bicolor) or wild Sorgh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Sorghum, an important feed for ruminants around the world and widely grown in Asia and Africa, also contains a cyanogenic glycoside, dhurrin, which has been shown to be rapidly hydrolyzed by the microbiota in the rumen of ruminants to release toxic HCN leading to animal toxicity. Investigations have shown that HCN content in fresh reclaimed sorghum is greater than 801 mg/kg, which is greater than the safety threshold of 200 mg/kg. , In 2022, there were cases of cattle dying after feeding hay containing sorghum on many farms in northwestern Italy, and the pathological results clearly indicated cyanide poisoning . This suggests that reducing the HCN content to below the safe threshold when handling feed can solve this problem.…”
Section: Part 1: Detoxification Of Cyanide In Feed and Foodmentioning
confidence: 99%
“…Sorghum, an important feed for ruminants around the world and widely grown in Asia and Africa, also contains a cyanogenic glycoside, dhurrin, which has been shown to be rapidly hydrolyzed by the microbiota in the rumen of ruminants to release toxic HCN leading to animal toxicity. Investigations have shown that HCN content in fresh reclaimed sorghum is greater than 801 mg/kg, which is greater than the safety threshold of 200 mg/kg. , In 2022, there were cases of cattle dying after feeding hay containing sorghum on many farms in northwestern Italy, and the pathological results clearly indicated cyanide poisoning . This suggests that reducing the HCN content to below the safe threshold when handling feed can solve this problem.…”
Section: Part 1: Detoxification Of Cyanide In Feed and Foodmentioning
confidence: 99%